Microbes without frontiers: severe haemolytic-uraemic syndrome due to E coli O104:H4. (21st December 2012) - Binks, Sophie; Regan, Kate; Richenberg, Jonathan; Chevassut, Tim
Abstract : Antibiotic use in infection with Shiga-toxin-producing strains of Escherichia coli ( E coli ) is thought to increase the risk of developing haemolytic-uraemic syndrome (HUS). One paediatric study concluded that E coli O157:H7-infected patients who had received antibiotic therapy were 17 times more likely to progress to HUS than those who had not. Quinolones are among those incriminated. In vitro experiments suggest toxin induction of 80-fold with ciprofloxacin and E coli O104:H4. We report here the case of a 44-year-old man returning from Hamburg who presented with a 5 day history of bloody diarrhoea which had worsened after starting ciprofloxacin. A severe illness of overlapping HUS and thrombotic thrombocytopaenic purpura (TTP) ensued, with neurological complications requiring ventilation and intensive care admission. Stool sample eventually confirmed E coli O104:H4. Although the patient made a good recovery following treatment with haemofiltration and plasma exchange with fresh frozen plasma (FFP), ciprofloxacin may have exacerbated his clinical course.